Fragmentation and Audience Activity on Video-on-Demand Platform: Netflix and the ‘Binge-watching’ - Reisa, Steffiani; Irwansyah, Irwansyah (School of Communication - Atma Jaya Catholic University of Indonesia, 2020)
One of digital transformation of television systems is an interactive service called video-on-demand (VOD). VOD provides full control to its users, by allowing viewers to enjoy, choose, store, and even download the desired audio-visual content anytime and through any electronic communication device. The presence of Netflix and other VOD service providers is transforming people's behavior patterns in watching television. People are beginning to switch to watching audiovisual content and episodes the same televisions or programs known as binge-watching through online streaming. This study focused on the concept of audiences’ activities based on Levy and Windahl’s typology model. The study also explored the motivation that was a part of uses and gratification theory. This new audience habit and motivation were explored by qualitative approach. The interview was conducted to the Netflix subscribers in Jakarta to discover the behavior activities and motivation of binge-watching. The thematic analysis was applied to analyze the process of fragmentation and audience activity that occurs in a very active new media society.